Original paperHouse-dust mite allergy: mapping of Dermatophagoides pteronyssinus allergens for dogs by two-dimensional immunoblotting - Martins, Luís Miguel Lourenço; Marques, Andreia Grilo; Pereira, Luísa Maria Dotti Silva; Goicoa, Ana; Semião-Santos, Saul José; Bento, Ofélia Pereira (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Introduction: Specific immunotherapy has shown to be very useful for allergy control in dogs, with a common success rate ranging from 65% to 70%. However, this efficacy could probably be improved and the identification of individual allergomes, with the choice of more adequate molecular allergen pools for specific immunotherapy, being the strategy. Aim : To map Dermatophagoides pteronyssinus (Der p) allergens for mite-sensitized atopic dogs, for better understanding how individual allergograms may influence the response to house-dust mite immunotherapy. Material and methods: To identify the Der p mite allergome for dogs, 20 individuals allergic to dust-mites and sensitized to Der p, were selected. The extract from Der p was submitted to isoelectric focusing (IEF), one-dimensional (1-D) and two-dimensional (2-D) sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). Separated proteins were blotted onto polyvinylidene difluoride (PVDF) membranes and immunoblottings were performed with patient sera. Allergen-bound specific IgE was detected. Results : Eleven allergens were identified from isoelectric focusing (IEF), as well as from 1-D SDS PAGE. From 2-D SDS-PAGE, 24 spots were identified. Conclusions : Several similarities were found between dog and human allergograms and no absolute correlation between sensitization and allergy was observed either. As in humans, different individual allergograms do not seem to implicate different clinical patterns, but may influence the response to specific immunotherapy. The molecular epidemiology approach in veterinary allergy management, by the characterization of individual patients’ allergoms and by choosing the best molecular allergen pool for each patient could also improve the efficacy of allergy immunotherapy.